(untitled) (Research, Society and Development, 2021)
The essential oil from C. aurantium has been widely studied due to its potential anxiolytic action on several receptors in the Central Nervous System (CNS). Although it presents variations in its phytochemical composition depending on its origin, we can highlight that many compounds remain present, such as linalool that demonstrated antagonistic activity on glutamatergic receptors, possible inhibitory action of noradrenaline and serotonin receptors, besides the ability to activate GABA receptors in association with some flavonoids present in the oil. It is globally known that the underlying pathology called anxiety influences worldwide as an antecedent of conflicting psychological and physical disorders, which are associated with various neuronal disorders. In this regard, the oil extracted from C. aurantium flowers shows a potential therapeutic application for the treatment of anxiety disorders. However, more studies are needed to elucidate its complete role on the CNS and to verify and prove its safety and efficacy profile.